Evolution of black shale sedimentary environment and its impact on organic matter content and mineral composition: a case study from Wufeng-Longmaxi Formation in Southern and Eastern Sichuan Basin - Yang, Xinrui; Yin, Hongchuan; Yang, Licheng; Xu, Liangjun; Chen, Junyu; Liu, Dongxi; Jiang, Chan; Jiang, Zengzheng (Frontiers in Environmental Science, 2024)
Due to global geological events and differences in regional sedimentary environments, marine shale reservoirs of Wufeng-Longmaxi Formation in Eastern and Southern Sichuan Basin exhibit significant heterogeneity in organic matter content and mineral composition. In order to reveal the influence of paleoenvironment evolution on reservoir heterogeneity, key geochemical indicators of elements were used to reconstruct the sedimentary environment of marine shale in Eastern and Southern Sichuan Basin. The influence mechanism of paleoenvironment on organic matter content and mineral components was also explored. The results indicate that the Wufeng-Longmaxi Formation in the Southern and Eastern Sichuan Basin can be divided into two third-order sequences (Sq 1 and Sq 2). Each third-order sequence is divided into a transgressive system tract (TST) and a highstand system tract (HST). The average TOC content in the Eastern Sichuan Basin is the highest during the TST1 period with reaching 4.2%, while reached its maximum at 3.9% during the TST2 period in the Southern Sichuan Basin. Due to the influence of high paleo-productivity, the organic matter accumulation and quartz content in the eastern Sichuan region were higher than those in the southern Sichuan region from the TST1 to the middle TST2 period. However, the organic matter accumulation and quartz content in the late TST2 period were lower than those in the southern Sichuan region due to the dilution of terrestrial debris. During the HST2 period, due to the influence of higher paleo-productivity, clay adsorption and preservation condition, the TOC content in the eastern Sichuan region slightly increased in the early stage. At the same time, the marine shale in the southern Sichuan region has a high content of quartz minerals and a low content of clay minerals due to strong weathering intensity and input of coarse-grained debris (silt-size quartz).